PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA POLRESTABES SEMARANG - Kusnul Khotimah, 14.05.51.0182; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the influence of Transformational Leadership Style, Motivation and Communication on Employee Performance. The object of research in this paper is POLRESTABES Semarang. The sampling technique in this study is to use probability sampling technique with the number of respondents 80 people. Data analysis used includes validity test with product moment, reliability testing with alpha coefficient (Cronbrach Alpha), multiple regression analysis, t test to test and prove the research hypothesis. The results of the research are (1) Transformational Leadership Style influences not influence on employee performance. (2) Motivation has a positive and significant effect on employee performance. (3) Communication has a negative effect on employee performance. Keywords :Transformational Leadership Style, Motivation, Communication and Employee Performance.